EFFECTIVENESS OF PAI LEARNING DESIGN USING THE ADDIE MODEL ON ACADEMIC ENGAGEMENT AND STUDENT LEARNING ACHIEVEMENT - Ulumuddin, Ulumuddin (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
This means that the results of studying PAI must be applicable in everyday life, both in the context of implementing religious rituals, as well as in behaving according to religious guidance/teachings so that the objectives of learning PAI are achieved. This research method uses descriptive qualitative research case studies at schools in the Probolinggo district. Paradigm shifts in education are becoming increasingly important due to world demands that continue to grow, both in terms of economic, social, and technology. The traditional educational model, which focuses on instruction-based learning and factual knowledge, is no longer sufficient to face complex and multidimensional future challenges. Paradigm shifts in education refer to fundamental changes in the way we view and carry out the learning process. Traditional paradigms that focus on factual knowledge, academic achievement, and teacher-centred learning have proven insufficient to prepare young people for a changing world. In the era of globalization and technological revolution, the need for 21st century skills such as critical thinking, creativity, collaboration, communication and digital literacy is becoming increasingly important